The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1177/1062860618791305
|View full text |Cite
|
Sign up to set email alerts
|

Can Medical Students Lead Effective Quality Improvement Initiatives? A Systematic Review

Abstract: Quality improvement project (QUIP) concepts are becoming embedded into medical school curricula, with many students now expected to conduct a QUIP as part of their progression. This study aimed to assess whether student-led QUIPs can be effective and sustainable. A systematic literature search was conducted using 5 databases: MEDLINE, Embase, Ovid, CINAHL, and PsycINFO. The authors searched for articles published between January 28, 1978, and January 28, 2018. In all, 3965 articles were identified through data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
(71 reference statements)
0
4
0
Order By: Relevance
“…Existing literature demonstrates both the benefits and challenges associated with student-led initiatives. There is evidence of student-run electives and journal clubs resulting in positive short-term outcomes [ 38 - 40 ]; however, medical schools need to focus more on equipping students with proper skills and resources for effecting long-lasting advancements [ 41 ]. One major challenge faced by student-led groups is recruiting and transitioning leadership between successive class years, which results in continuity gaps in provided activities from year to year.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature demonstrates both the benefits and challenges associated with student-led initiatives. There is evidence of student-run electives and journal clubs resulting in positive short-term outcomes [ 38 - 40 ]; however, medical schools need to focus more on equipping students with proper skills and resources for effecting long-lasting advancements [ 41 ]. One major challenge faced by student-led groups is recruiting and transitioning leadership between successive class years, which results in continuity gaps in provided activities from year to year.…”
Section: Discussionmentioning
confidence: 99%
“…Reviews of QI projects published in manuscript form have used SQUIRE or similar rating systems to describe limitations in projects' scientific quality. For example, Sayma et al 6 found that among QI projects led by medical students, the mean SQUIRE score was 6.5 of 10 (range 0-10) among 21 included publications. Forman-Hoffman et al 19 used a study quality assessment process tailored to QI projects to rate the strength of evidence of 19 studies on pediatric mental health care interventions, finding that all but one had low or insufficient strength of evidence for all outcomes reviewed.…”
Section: Discussionmentioning
confidence: 99%
“…13 Anticipating missing data on key elements of project methods, the team did not evaluate scientific quality of projects based on a checklist such as Standards for Quality Improvement Reporting Excellence (SQUIRE). 6 The total number of cases analyzed was counted over the implementation period to reflect the scope of project implementation rather than the analysis of baseline data. Likewise, project duration was tracked from the date of the earliest implementation to the date data collection was completed for analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing literature demonstrates both the benefits and challenges associated with student-led initiatives. There is evidence of student-run electives and journal clubs resulting in positive short-term outcomes [38][39][40]; however, medical schools need to focus more on equipping students with proper skills and resources for effecting long-lasting advancements [41]. One major challenge faced by student-led groups is recruiting and transitioning leadership between successive class years, which results in continuity gaps in provided activities from year to year.…”
Section: Call For Action: Increased Interest In Iandt Among Medical S...mentioning
confidence: 99%